Assessment of PMTCT Success Rates Based on Antiretroviral Interventions and Feeding Options: A Prospective Cohort Study - Kolawole A. Fasakin, PhD; Christopher T. Omisakin, Msc; Idowu O. Adebara, MBBS, FMCOG; Wasiu A. Ajetunmobi, MBBS, FWACPaed; Adebayo A. Adeniyi, MBBS, FMCOG, FWACOG; Ayodele J. Esan, Msc; Olufunke B. Bolaji, MBBS, FMCPaed; Oluwafemi D. Ajayi, Msc; Abayomi J. Afe, MBBS, MPH, Ph.D, MRCOG (Global Health and Education Projects, Inc., 2018)
Background: The success of any prevention of mother-to-child transmission (PMTCT) program is assessed by the proportion of HIV-exposed infants that sero-convert at the end of all risk exposures. Although adopting the best feeding option for HIV-exposed infants is one of the factors that impact PMTCT outcomes, there is limited data on the assessment of PMTCT success rates based on antiretroviral interventions and feeding options. This study assesses the success rate of PMTCT service based on antiretroviral interventions and feeding options. Methods: Eighty-five HIV-infected mothers previously in care were enrolled in a prospective cohort study. Folders and structured questionnaires were used to extract data on mother-infant pair and the first CD4, count of infected mothers on enrolment at PMTCT clinic. Dry blood spot samples were obtained from exposed infants for early infant diagnosis. Results were analyzed using the SPSS software. Results: The mean age of enrolled mothers was 31.3 ± 4.4 years, and an average CD4+ T-lymphocyte count of 368.6 ± 216.2 cells/µl. Seven (8.2%) of the HIV-exposed infants were positive for HIV-1 based on early infant diagnosis results. Overall PMTCT success rate (PMTCTSR) was 91.8%. HIV-1 prevalence of 5.0%, 0% and 21.1% was found among infants of patients who opted for breastfeeding, replacement feeding, and mixed feeding respectively thus yielding PMTCT success rates of 95%, 100% and 78.9%. Pediatric antiretroviral interventions success rates in HIV-exposed infants was 95.8%, 80.0% and 66.7% based on age groups ≤ 6 months, > 6 ≤ 12 months, and > 12 ≤ 18 months respectively. Conclusion and Global Health Implications: Quality PMTCT service is vital for successful prevention of mother-to-child transmission of HIV. Implementation of more dynamic approaches such as adherence to option B+ guidelines in PMTCT service in our settings can further reduce mother-to-child transmission of HIV and improve outcomes. Key words: Assessment, Antiretroviral Interventions, PMTCT, Success Rates, Feeding Options, Cohort  Copyright © 2018 Fasakin et al. This is an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.